(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article presents a classification of finely dispersed mineral fillers used in cement system technology, taking into account their origin, chemical-mineralogical composition, and reactivity. A comparative analysis of the influence of the most common types of aggregates - microsilica, fly ash, metakaolin, and limestone flour - on the physical-mechanical and operational characteristics of cement composites was conducted